Mycoparasitic Activity of Indigenous Trichoderma virens Strains Against Mungbean Soil Borne Pathogen Rhizoctonia solani: Hyperparasite and Hydrolytic Enzyme Production - Alfi Inayati; Liliek Sulistyowati; Luqman Qurata Aini; Eriyanto Yusnawan (AGRIVITA, Journal of Agricultural Science, 2020)
Rhizoctonia solani is one of the harmful pathogens on mungbean, which is very challenging to be controlled. T. virens has been studied intensively and has great potency to control R. solani through mycoparasitism. Seven strains of T. virens isolated from various rhizospheres were tested for their mycoparasitic potential by observing their hyperparasitism and the production of hydrolytic enzymes. All strains showed the ability to suppress the growth of R. solani on dual culture assay as well as on culture filtrate test with the inhibition ability from 43.8 to 68.6% on the dual culture assay and from 22.2 to 71.1% on the culture filtrate assay. Inter-fungal interaction, which was observed by an electron microscope, showed hyperparasitic action of T. virens against R. solani involved the formation of the knob-like structure followed by the growth of Trichoderma hyphae inside host mycelia, coiling, lysed cell wall, and swollen of mycelial tips. Mycoparasitism of T. virens also correlated with the synthesis of hydrolytic enzymes, such as cellulase and chitinase, which influenced the overall hyperparasitic ability of T. virens against the pathogen. Based on in vitro assay, the Tv3 strain proposed as a promising strain to control R. solani due to its high growth inhibition and relatively high cellulase and chitinase productionse.